Potensi Beberapa Tanaman Herbal di Indonesia Sebagai Antidiare Berdasarkan Penelitian In Vivo - Hartanti, Yesiska Kristina; Rosa, Dela; Mailinda, Putri; Elleanore, Angeline; Deis, Friska (Jurnal Farmasi & Sains Indonesia, 2023)
The gastrointestinal tract facilitates the primary function of the body, such as food digestion and absorption. Disruption of the process will lead to digestive tract disorder. One disorder of the digestive tract is diarrhea. Diarrhea is a condition of loose and watery stool that excretes more frequently than normal, accompanied by abdominal cramps. Herbal plants research as a therapy alternative has been continuing to develop for herbal medicine potential discovery. From the literature study, it was found 9 species of plants have activity to inhibit diarrhea based on in vivo study. This article will expose the various natural properties found in Indonesia.